(untitled) (Applied Biological Research, 2011)
Field experiments were conducted during kharif seasons of 2006 and 2007 at Rice Research and Regional Station, SKUAST-K, Khudwani, Anantnag (India) on a silty clay loam soil, normal in reaction. The study revealed that herbicides flufenacet @ 90 g ha-1, application of butachlor 1.5 kg followed by chlorimuron ethyl + metsulfuron methyl 4 g ha-1and butachlor 1.5 kg followed by bensulfuron methyl 50 g ha-1recorded significantly higher number of panicles, grains panicle-1and grain and straw yields through better weed control as indicated by lower weed density and reduced weed dry matter as compared to other herbicidal treatments. On an average, flufenacet application gave 8.1 and 46.7% more grain yield over butachlor and weedy check treatments, respectively. Chlorimuron ethyl + metsulfuron methyl provided good control of broad leaved weeds and sedges, while bensulfuron-methyl was effective against sedges.